2015
DOI: 10.11144/javeriana.sc20-3.arol
|View full text |Cite
|
Sign up to set email alerts
|

A review of longnose skates Zearaja chilensis and Dipturus trachyderma

Abstract: Longnose skates may have a high intrinsic vulnerability among fishes due to their large body size, slow growth rates and relatively low fecundity, and their exploitation as fisheries target-species places their populations under considerable pressure. These skates are found circumglobally in subtropical and temperate coastal waters. Although longnose skates have been recorded for over 150 years in South America, the ability to assess the status of these species is still compromised by critical knowledge gaps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 180 publications
0
19
0
Order By: Relevance
“…In these cases, the amplified fragments from cox1 gene did not provided enough information to establish phylogenetic relationships in the species studied; mainly due to the use of technologies now considered obsolete, their inability to develop species-specific primers, and the inherent evolutionary close-proximity of longnose skates (Díaz de Astarloa et al, 2008;Naylor et al 2012a, b;Vargas-Caro et al, 2015, 2017. Sequences of all mitochondrial loci amplified in the present study showed over 98% identity and a low number of -82-based on morphology Moura et al, 2008;Toffoli et al, 2008;Ward et al, 2005Ward et al, , 2007Ward et al, , 2008Ward et al, , 2009Wong et al, 2009;Zemlak et al, 2009).…”
Section: Molecular Tools For Longnose Skates Identificationmentioning
confidence: 99%
See 4 more Smart Citations
“…In these cases, the amplified fragments from cox1 gene did not provided enough information to establish phylogenetic relationships in the species studied; mainly due to the use of technologies now considered obsolete, their inability to develop species-specific primers, and the inherent evolutionary close-proximity of longnose skates (Díaz de Astarloa et al, 2008;Naylor et al 2012a, b;Vargas-Caro et al, 2015, 2017. Sequences of all mitochondrial loci amplified in the present study showed over 98% identity and a low number of -82-based on morphology Moura et al, 2008;Toffoli et al, 2008;Ward et al, 2005Ward et al, , 2007Ward et al, , 2008Ward et al, , 2009Wong et al, 2009;Zemlak et al, 2009).…”
Section: Molecular Tools For Longnose Skates Identificationmentioning
confidence: 99%
“…There are few species of cartilaginous fishes considered target species in coastal and oceanic fisheries in the southeast Pacific Ocean (Bustamante et al, 2014b), although the longnose skates Zearaja chilensis and Dipturus trachyderma are of considerable commercial importance in Chilean waters (Lamilla et al, 2010;Vargas-Caro et al, 2015;SERNAP, 2015). Several authors have carried out taxonomic revisions and produced identification guides which include aspects of the morphology and biology of both species (see Vargas-Caro et al, 2015); however, the identities of Z. chilensis and D. trachyderma are still confused in landing records due to similarities in body shape and colour (Vargas-Caro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations